Two Wheeled Robot Self Balancing Control Research - Ni Dan; Jingfang Wang (Institute of Advanced Engineering and Science, 2016)
According to movement balancing and position control problem of Self Balancing Two Wheeled Robot, a method based on H∞ Robust Control was proposed. We apply it onto the MIMO nonlinear model of robot, and simulated it in the MATLAB environment The simulation results shows that the robot can be balanced in fixed position well by this method, and also it have the ability to anti interference.